A religiosidade dos sem religião = The religiosity of those without religion - Luiz, Ronaldo Robson (Ciencias sociales y religión, 2013)
According to data from the IBGE - 2010 Census, there are 12 million religious people in Brazil who are not part of the traditionally known instituted religions. There are no religion in Brazil. The information from the Census also points to the increasing quantity of this specific group, which is accounted for in about 7.4% of the Brazilian population. These, according to Pierucci (2004) can be defined as those who are disengaged from any religion, disenfranchised from any and all religiously constituted authority. These people are not atheists, they believe in God, they are even proud of their strong connection with the transcendental. The fact is that they are not linked to any particular religion. Generally, such people have already gone through some religions, but did not find satisfaction in them, having opted for an “autonomous relationship with God”, where in the words of Arriel (2004) it is the influence of individualism, the cult of the autonomous subject, body and well-being, where what is at stake is the affirmation of self-identity. The purpose of this article is to analyze the religiosity (s) of non-religion in contemporary times.